Media Coverage of Campaigns: A multilevel study of Mexican women running for office (Communication & Society, 2020)
Previous studies on the United States and Latin America have demonstrated unequal media coverage of men and women during electoral campaigns. However, in Mexico, a country where women increasingly participate in politics, this has seldom been studied. This is worrisome when considering that, with gender stereotyping, the media can create new barriers for female candidates, affecting voters’ perceptions of women’s expertise and policy proposals. Through a comparative analysis, this research explores the role of the media when covering women running for office. It specifically studies coverage of executive-branch campaigns at the three levels of government. This is an important contribution to the literature as there are few studies of the Mexican context; specifically, this research examines the visibility, focus, traits, and issues covered in written media in order to explore, as well expand knowledge of, media biases and Mexican politics. Findings suggest that women running for positions with more power received different appraisal in printed media. Furthermore, male candidates received more coverage with the number of stories and headlines explicitly covering them higher than female candidates. This was most evident in municipal elections. At the same time, coverage of both female and male candidates shied away from personal traits or family matters. The media’s attention was on ‘male’ issues, where women were less competitive than men. Albeit with marginal differences, coverage of municipal elections was positive for women (where they won), compared with that of the across-the-board losses for female candidates running for governor.